Numerical and analytical study of delamination in composite laminates. (1st January 2012) - Harvey, C.M.; Wang, S.
A robust numerical method is developed to study delamination in composite beam structures under lateral and axial loads. A tensor symmetrisation technique is used to formulate the beam element based on the Euler beam theory with full geometrical non-linearity to achieve high computational efficiency. Ply interfaces are modelled with high-stiffness springs. It is found that the beam element suffers from membrane locking for non-symmetric laminates. A method is found to overcome it. The model is used to simulate double cantilever composite beam structure tests and end notched flexure tests. Excellent agreement is observed with analytical and existing numerical and experimental data. The model is also used to study the buckling, post-buckling and delamination propagation in moderately thick composite beams. Satisfactory agreement is demonstrated between the present predictions and existing numerical and experimental data. It is noted that the through-thickness shear effect is significant for moderately thick composite laminates.